Mechanical and Morphology Properties of Egg-Shell Powder (ESP) Filled Low Density Polyethylene Composites - Siti Shuhadah; Supri, A. Ghani; Kamarudin, Hussin (Universiti Kuala Lumpur (UniKL), 2010)
Organized by Universiti Kuala Lumpur (UniKL), 27th - 28th November 2007 at Kuala Lumpur, Malaysia.